Preservation of the intellect: developing research skills among IIUM undergraduates - Eid, Iyad Muhammad; Rokis, Rohaiza; Syed Hussien, Sh Fatimah Alzahrah; Sulaiman, Szariannie (Universitas Negeri Surabaya, 2020)
The purpose of this paper is to prove that undergraduates have the capacity to be engaged in conducting empirical research and generating knowledge. It discusses the outcomes of a recent research training programme offered to undergraduates at the International Islamic University Malaysia. The training programme was organized and conducted by the Department of Sociology and Anthropology. As of early 2020, about 700 undergraduates, including those studying at different departments at the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) have been trained. Working in teams, the undergraduates produced remarkable research projects presented in the form of written reports, oral presentations, and open discussions. To document these papers, the first social research collection book titled “Khalduniyyat” was submitted to the respective faculty, KIRKHS, for review and publication. This paper is based on a qualitative research approach, employing semi-structured interviews with fifteen academics who supervised or attended the training activities. Further, the paper reflects on the feedback provided by the trainees. The originality of this research paper is presented by showing how the programme explored and enhanced the intellectual capabilities of IIUM undergraduates, that resulted in the enhancement of their research skills equivalent to postgraduate level.